Knowledge and attitude of healthcare providers towards prenatal diagnosis of sickle cell anaemia in University College Hospital, Ibadan, Nigeria (2014)
The purpose of this study was to examine the knowledge and attitude of health professionals towards prenatal diagnosis of sickle cell anaemia in UCH Ibadan, Nigeria. The study also aimed at knowing the impact of culture and religion on the attitude of healthcare professionals towards prenatal diagnosis. The descriptive survey design was adopted for the study; 618 respondents purposively sampled among nurses, doctors and laboratory scientists were used. The results revealed that healthcare providers have good knowledge of prenatal diagnosis and availability of prenatal diagnostic facilities in the country; and that religion and culture should be considered if prenatal diagnosis will be used as a means of controlling sickle cell anaemia. It concluded that genetic counseling with prenatal diagnosis could be a reliable way of curbing the menace of sickle cell anaemia.